Does government and institution quality matter to sustainable development goals? - Har, Wai Mun; Law, Siong Hook; Sek, Siok Kun; Mazlan, Nur Syazwani; Ahmad, Mohd Naseem Niaz (Penerbit UMT, 2023)
The world needs to be more resolute to meet its pledge to achieve the United Nations Sustainable Development Goals by 2030, yet three issues remain. Firstly, the representation of sustainable development is often not the SDG. Secondly, the determinants of sustainable development are not conclusive. Thirdly, there are incongruent relationships within components of institutional quality, thus casting scepticism on the validity of the aggregated relationship. This paper aims to analyse factors affecting the achievement of the Sustainable Development Goals Index (SDGI) through a novel attempt based on the recomposed institutional quality. In high-income countries, the most important determinants of sustainable development come from higher capital investment, higher government fiscal expansion, and upholding democracy. In middle-income countries, government effectiveness is the most important determinant of sustainable development. In low-income countries, government plays a vital role through fiscal expenditure and good institutional quality but provided the sustainable development level is high”anomalies results in control of corruption, government ineffectiveness, and voice and accountability prompt for attention.